Correlation of Hand Grip Strength and Body Height Amongst Young Adults in Indonesia - Peppy Nawangsasi (Fakulti Perubatan dan Sains Kesihatan, Universiti Putra Malaysia, 2021)
Introduction: Hand grip strength (HGs) is an anthropometric measure of musculoskeletal performance, which might predict any functional limitation and disability. Increased body height (Ht) is arguably correlated to the increase in number and length of the muscle fibers may modify the HGs. We determine correlation between the HGs and the Ht among seemingly healthy Indonesian young adults. Methods: The HGs of both hands (using CAMRY EH101 digital hand dynamometer) and the Ht (using GEA stature meter for height) of 16 males and 16 females aged 20 to 26 years old were measured. Data were analyzed using SPSS 25.0 (variables differences between genders were tested using Mann-Whitney U test; correlation between variables with Pearson or Spearman correlation tests). Level of significant was p< 0,05. Results: The correlation between Ht and HGs was moderate (r = 0.545, p < 0.05) for dominant hand and (r = 0.597, p < 0.05) non-dominant hand. There is no significant correlation between dominant HGs with Ht in males (r = -0,292, p 0,273) and females (r = -0.266, p 0,319), and also happens in non-dominant HGs with Ht in males (r = -0,396, p 0,129) and females (r = -0,005, p 0,985). Conclusion: HGs had significant correlation with Ht; hence in determining and assessing results of HGs in the young adults, body height should be considered.